Denosumab treatment of inoperable or locally advanced giant cell tumor of bone – Multicenter analysis outside clinical trial. Issue 9 (September 2018) - Rutkowski, Piotr; Gaston, Louie; Borkowska, Aneta; Stacchiotti, Silvia; Gelderblom, Hans; Baldi, Giacomo Giulio; Palmerini, Emanuela; Casali, Paolo; Gronchi, Alessandro; Parry, Michael; Campanacci, Domenico Andrea; Scoccianti, Guido; et al.
Abstract: Background: Giant cell tumor of bone (GCTB) is an osteolytic, locally aggressive, rarely metastazing bone tumor. This is a retrospective study evaluating a large series of GCTB patients treated with denosumab in routine practice in 6 European reference centers. Methods: Patients with locally advanced, unresectable or metastatic GCTB, treated with denosumab outside clinical trials were eligible. Primary end-point was progression-free survival (PFS) for all patients; secondary end-points were: type of surgery, relapse rate and event-free survival for patients after preoperative denosumab + surgery. Results: We identified 138 patients treated in the period 2011–2016. In 40/43 cases the diagnosis was confirmed by H3F3A gene mutation. Median follow-up time was 23 months (range 6–48). Primary tumor was located in lower limb (38%) - mostly in femur and tibia, in upper limb (34%), and in pelvis/axial skeleton/ribs (28%). 110 (80%) patients had primary tumors, 28 (22%) recurrent tumors after previous surgical procedures (+/− radiotherapy). 89/138 patients had locally advanced GCTB and underwent neoadjuvant denosumab. The median denosumab treatment duration was 8 months (median number of cycles 11), 98% had clinical benefit from therapy. 39 (44%) had wide en-bloc resection - WE (+implantation of the prosthesis in 17 cases), the other 50 (56%) cases had intralesional curettage - C. Progression after surgical treatment was observed in 19 patients, 16 of them after C (32%); 13 patients underwent denosumab re-challenge, and all responded. Two-year progression-free survival (PFS; from denosumab start) rate was 81%; 2-year EventFS (from surgery) was significantly better in WE group (93%) vs 55% in C group (p = 0.006). Treatment was well tolerated with only 2 cases of grade 3 toxicity and one osteonecrosis of the jaw. Conclusion: Our retrospective study confirms that denosumab is extremely efficient in unresectable/metastatic disease as well as in a neoadjuvant setting. Our data confirm excellent efficacy and short-term tolerability of this drug. Our data suggest that neoadjuvant therapy with denosumab is the option for treatment of initially locally advanced tumors to facilitate complete surgical resection or avoid mutilating surgery. The risk of recurrences after curettage of GCTB following denosumab raises questions about the optimal management of such cases.